Biblical Servant Leadership An Exploration of Leadership for the Contemporary Context - Crowther, Steven (Christian Faith Perspectives in Leadership and Business, 2018)
This book explores the concepts from Scripture for Servant leadership and compare these findings with contemporary models of servant leadership. It is an examination of Christian leadership for the contemporary world in its global and increasing secular context. Leadership studies typically view leadership externally from the results. This is a good beginning but leadership needs to also view the inside of leadership in the person of the leader. Scripture is uniquely qualified in this area since its first concern is the person who leads not just in leadership behaviors. The author uses examples from both the Old and New Testament to establish a new shepherd model of leadership that moves beyond the servant mode to the mode of caring direction. This model will provide scholars and researchers as well as leaders themselves with a way of leading that overcomes negative forms of leadership which lead to failure.